The perspective of implementing the Smart home living concept among potential homebuyers in Klang Valley - Chan, Eng Kean (2024)
As technology continues to evolve, humans have devised innovative systems like Smart Home Living to enhance comfort and living standards. This system has revolutionized traditional housing designs, aiming to provide a space that not only offers comfort but also maximizes benefits and convenience.